2001
DOI: 10.1108/eum0000000007088
|View full text |Cite
|
Sign up to set email alerts
|

A user study of the design issues of propie: a novel environment for enhanced interaction and value‐adding of electronic documents

Abstract: In this paper, we present a proposed information environment (PROPIE) for enhanced interaction and value‐adding of electronic documents (e‐documents). The design of PROPIE was based on a thorough user needs and requirements assessment in interacting with information through well‐documented findings, and a focus group with twelve participants to elicit features that were deemed desirable in future interactions. The design was also based on an earlier work which reviewed the advancements in various user interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The derived set of interaction and information object properties has been reported and discussed in detail in an earlier work [1]. The PROPIE evaluation comprises three tiers of evaluation and tiers 1 and 2 results have been reported [2,3]. In this paper, we consolidate all the evaluation results and outline the major findings of the research.…”
Section: Research Aims and Objectivesmentioning
confidence: 88%
“…The derived set of interaction and information object properties has been reported and discussed in detail in an earlier work [1]. The PROPIE evaluation comprises three tiers of evaluation and tiers 1 and 2 results have been reported [2,3]. In this paper, we consolidate all the evaluation results and outline the major findings of the research.…”
Section: Research Aims and Objectivesmentioning
confidence: 88%
“…The PROPIE evaluation comprises three tiers of evaluation and tiers 1 and 2 results have been reported [2,3]. In this paper, we consolidate all the evaluation results and outline the major findings of the research.…”
Section: Research Aims and Objectivesmentioning
confidence: 91%
“…In an online exhibition site, for instance, users can specify a query against a set of exhibit artefacts, navigate an exhibition with the aid of visual clues about what items are available and where they are in the virtual space, and obtain detailed information via a zooming mechanism. The evaluation carried out in the study by Liew et al (2001) also show that users welcome features that allow them to create and save digital comments and attach these to a document, an image, an artefact, etc., and to be able to return to these, and to share these with other users.…”
Section: User Interfacementioning
confidence: 98%
“…An earlier empirical study examining users' interaction in an electronic environment (Liew et al, 2001) has also shown that an integrated suite of appropriate interactive tools for querying, navigating, organising and authoring information can add value to users' browsing and searching experience. In an online exhibition site, for instance, users can specify a query against a set of exhibit artefacts, navigate an exhibition with the aid of visual clues about what items are available and where they are in the virtual space, and obtain detailed information via a zooming mechanism.…”
Section: User Interfacementioning
confidence: 99%